Whose is it anyway? - Abd Razak, Dzulkifli (2009)
THE recent spat over the cultural claims by Indonesia offers another dimension on the understanding of the 1Malaysia concept. First and above all, it boils down to our weakness, if not failure, to articulate what precisely is Malaysian culture, which now assumes a rather amorphous dimension given the multicultural dimensions of the Malaysian cultural horizon. If it is to be "Truly Asia", then which Asia? Including Indonesia? Not any more it seems.